Subsidising formal childcare versus grandmothers' time: Which policy is more effective? - Victoria Osuna-Padilla (Economics: The Open-Access, Open-Assessment Journal, 2021)
This article quantifies the relative effectiveness of childcare subsidies and subsidies on grandmothers' time on married mothers' employment and fertility rates, paying special attention to heterogeneous effects. A heterogeneous agent model, populated by married households who make decisions related to labour supply and fertility, and the Spanish economy are used as a benchmark for calibration. The results indicate that childcare subsidies conditional on employment are more effective than subsidies on grandmothers' time to foster the participation of married mothers in the labour force. However, they induce women to work fewer hours, unless after-school hours are also subsidised. This overtime subsidy is also necessary for the fertility rate to increase, but it implies a significant adjustment in tax rates to maintain the same fiscal balance. If the aim is simply to raise the employment rate of mothers of children aged 2 years or younger, then subsidising childcare costs only is more effective because the fiscal effort is lower. Regarding the heterogeneous effects, in all the policies studied, the growth in female employment is mainly accounted for by the behaviour of women without tertiary education while that of fertility is accounted for by women with tertiary education. Considerations related to inequality and distributional effects of these policies would also seem to favour childcare subsidies versus subsidies on grandmothers' time.
Keywords: J13; J18; J22; 330; childcare costs; childcare subsidies; female employment; fertility; grandmother childcare